MOBIL TEXNOLOGIYALAR JÁRDEMINDE PEDAGOGIKALÍQ PROGRAMMALÍQ QURALLAR JARATÍW - Qunnazarov, A.Q. (SCIENCE and SOCIETY, 2022)
The article describes mobile education, the pedagogical foundations of mobile education, WAP or GPRS technologies in mobile education, the history of development, mobile platforms, mobile applications, the MITApp Inventor 2 platform when creating mobile applications and their analysis.